Generalist versus specialist CEOs and acquisitions: Two-sided matching and the impact of CEO characteristics on firm outcomes - CHEN, Guoli (Institutional Knowledge at Singapore Management University, 2021)
Research Summary: To address endogeneity concerns stemming from firm-CEO matching, we deploy a two-sided matching model that identifies the complementarities arising from the CEO-firm match and subsequently account for these complementarities in empirical tests. Applying this approach, we examine how the nature of CEOs' human capital affects the acquisition behavior and performance of firms. We find that generalist CEOs (CEOs with a broader set of knowledge and skills) are more likely to engage in unrelated acquisitions than specialist CEOs (CEOs with a narrower but deeper set of knowledge and skills). We also find that the fit between the nature of CEOs' human capital and the type of acquisitions they undertake is associated with stronger performance. Our paper contributes to research on CEOs, human capital, M&As, and microfoundations. Managerial Summary: We deploy an empirical approach that takes into account the complementarities that arise from the matching of CEOs and firms when testing hypotheses on how CEO attributes shape firm outcomes. Based on this approach, our study finds that CEOs with a broader set of managerial knowledge and skills (generalist CEOs) are more likely to engage in unrelated acquisitions (acquisitions outside a firm's main industry) than CEOs with a narrower but deeper set of knowledge and skills that is more closely tied to a particular industry, firm, or domain (specialist CEOs). We also find that the fit between the nature of CEOs' human capital and the type of acquisitions they engage in is associated with stronger performance.